The limiting distribution of the mutual winding angles of particles in a Brownian stochastic flow with Lyapunov's zero top exponent - Kuznetsov, V. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
The investigation of geometrical properties of particles moving in stochastic flows leads to the study of the limiting behaviour of their mutual winding angles. This problem is solved for isotropic Brownian stochastic flows with zero top Lyapunov exponent.